RF TIMING TECHNIQUE AND ITS POSSIBLE APPLICATIONS - A. T. Margaryan
Experimental results that demonstrate principles of operation of a new RF timing technique at 500 MHz are presented. Two new devices based on these principles are considered: the radio frequency picosecond phototube and the time-zero fission fragment detector. Possible applications of the technique in high-energy elementary-particle and nuclear physics experiments as well as in applied physics are discussed
Keywords: Physics; Electromagnetism; electron and ion optics